Interactive Electronic Book (IE-Book) of Arabic Speech Material for Undergraduate Students - Amami Shofiya Al Qorin; Hanik Mahliatussikah; Kholisin Kholisin (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2022)
This research aimed to find students' and lecturers' needs for Arabic speech material design with an interactive electronic book (IE-Book) model for undergraduate students. Currently, books for this material are limited and do not fulfill the students' needs. This need analysis study used the descriptive analysis method: the data was collectedrom observation, interview, questionnaire, and other supporting documents. Then the data analysis technique used a judgment expert. There were four steps to analyze the data; data collection, data reduction, data display, and conclusion. This research indicated that 72% of the students had difficulty learning Arabic speech. At the same time, 73% of students struggle to make excellent and correct Arabic speech. IE-Book for Arabic public speaking design is the proper and best solution to be used as guidance for speech courses and learning processes in Arabic speaking material at universities based on the problem above and students’ needs analysis that showed the high level for designing of alternative materials.